Subclinical target organ damage in subjects with different components of metabolic syndrome - Oxana P. Rotar; Maria A. Boyarinova; Ekaterina V. Moguchaia; Ekaterina P. Kolesova; Anastasya M. Erina; Vladislav N. Solntsev; Alexandra O. Konradi; Eugene V. Shlyakhto (Clinical and Experimental Hypertension, 2018)
Background: To assess the association of metabolic syndrome (MS) and its components with target organ damage in a follow-up study of relatively healthy bank employers. Methods: Out of 1600 random samples of office workers in Saint Petersburg (Russia), a group of 383 participants with at least one component of MS and without cardiovascular complications was selected (mean age 46.6 ± 9.0 years, 214 females (64.6%)). Follow-up visit was performed in 331 subjects. Target organ damage (TOD) was assessed by echocardiography, carotid ultrasound, applanational tonometry, brachial–ankle index, and urine albumin excretion measurements. Anthropometry, vital signs, and biochemistry were performed according to standard protocols. Results: Presence of MS was not associated with higher probability of TOD. Multiple linear regression revealed significant association of all markers of TOD with older age. Hypertension was a significant predictor of left ventricular hypertrophy (LVH), increased arterial stiffness, and early signs of carotid atherosclerosis in logistic regression adjusted for age and gender. During follow-up, proportion of patients with LVH significantly decreased (from 46.7% to 32.9%, р = 0.003) and prevalence of patients with IMT > 0.09 сm increased (from 24.5% to 44.1%, p < 0.001) accompanying by significant declining of office blood pressure (BP) and total cholesterol. Conclusions: MS per se is not related to increased probability to TOD. Hypertension, female gender, and older age are main determinants of subclinical changes. After 2-years follow-up, significant LVH and renal damage regression was observed probably owing to BP reduction. Alternatively, early signs of carotid atherosclerosis increase with aging despite decreasing of the prevalence of hypercholesterolemia.